PENGARUH INTERNAL SERVICE QUALITY DAN INTERNAL CUSTOMER SATISFATION TERHADAP EMPLOYEE LOYALTY - Pramesti, Rahma Andita Desi; Hussein, Ananda Sabil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Employee loyalty is an important key for companies that want to survive and win the competition in business. This study aims to identify the effects of internal service quality and internal customer satisfaction on employee loyalty at PT. HashMicro Indonesia. This study is categorized as explanatory research, which can either accept or reject hypotheses based on the testing results. Using simple random sampling, 127 employees of the company were selected as the sample. This research uses instrument test and classical assumption test in SPSS 25. The data was analyzed using descriptive statistics and multiple linear regression. This research finds that internal service quality does not influence employee loyalty and that internal customer satisfaction affects employee loyalty. The results in this study can reveal how important the influence of internal customer satisfaction affects employee loyalty, so that companies or similar are expected to pay more attention to things that can increase employee satisfaction and measure employee satisfaction to achieve the highest level of employee loyalty.